ANALISIS PEMAHAMAN KEBHINEKAAN GLOBAL SISWA KELAS IV SEKOLAH DASAR - Dea Gita Tasya; Otib Satibi Hidayat; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the extent to which fourth grade students at SDN Kebon Manggis 01 understand global diversity. The background of this research is based on the importance of instilling the value of global diversity from an early age which includes respect for differences in ethnicity, religion, race and culture. This research uses a descriptive qualitative approach with data collection techniques in the form of interviews, participatory observation, and documentation. The results showed that students' understanding of global diversity is still at a basic stage and has not fully touched the aspects of attitude and application of values in everyday life. Some of the factors that influence this include a monotonous learning approach, lack of variety of learning media, and the influence of family and social environment. Therefore, a more varied, interactive and contextual learning strategy is needed to be able to instill the character of global diversity more effectively in elementary school students.